2000
DOI: 10.2135/cropsci2000.402493x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Production and Quality of ‘Tifway’ Bermudagrass as Affected by Seasonal Application Patterns of Trinexapac‐Ethyl

Abstract: maximum growth inhibition at 2 to 5 wk after PGR applications, along with improvements in turfgrass qual-Research on the gibberellic acid (GA)-inhibiting plant-growth regity. Existing concerns in the golf course industry with ulator (PGR) trinexapac-ethyl (TE) regarding seasonal effects of single vs. multiple applications of this product on turfgrass quality and PGR applications in bermudagrass include turfgrass distissue production has not been reported. Research was conducted at coloration 1 to 2 wk after ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 13 publications
10
64
0
Order By: Relevance
“…The smallest reductions resulted from prohexadione-calcium and bispyribac-sodium applied at the respective doses of 100 and 40 g ai ha -1 which were, respectively, of 49.6 and 38.9% at 119 DAA (Table 3). Fagerness and Yelverton (2000) All the plant growth inhibitors used in this study were verified to bring about significant reductions in inflorescence height at 119 DAA in comparison with the plants of the check treatment. The lowest value resulted when trinexapac-ethyl was applied at the dose of 904 g ai ha -1 when the inflorescence height was of 2.9 cm.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The smallest reductions resulted from prohexadione-calcium and bispyribac-sodium applied at the respective doses of 100 and 40 g ai ha -1 which were, respectively, of 49.6 and 38.9% at 119 DAA (Table 3). Fagerness and Yelverton (2000) All the plant growth inhibitors used in this study were verified to bring about significant reductions in inflorescence height at 119 DAA in comparison with the plants of the check treatment. The lowest value resulted when trinexapac-ethyl was applied at the dose of 904 g ai ha -1 when the inflorescence height was of 2.9 cm.…”
Section: Resultsmentioning
confidence: 76%
“…It is important to emphasize that although the injury levels caused by trinexapac-ethyl at the doses of 113 and 226 g ai ha -1 , prohexadionecalcium at 100 and 200 g ai ha -1 , and by bispyribacsodium at 40 g ai ha -1 were statistically similar to those of the check treatment plants, they may be considered as unacceptable if lawns with good visual aspect are to be the objective (FAGERNESS; YELVERTON, 2000;McCARTY et al, 2004;McCULLOUGH et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…ha -1 , Costa et al (2009) found reductions from 49.2 to 55.6%, respectively, in the production of dry mass of 'Meyer' zoysiagrass. Fagerness & Yelverton (2000) explained that a single application of trinexapac-ethyl at 107 g a.i. ha -1 caused a 40% reduction in the production of tissues in Tifway bermudagrass.…”
Section: O N T R O L C O N T R O Lmentioning
confidence: 99%
“…In contrast, high doses provide better results for longer periods, but with higher levels of injury. This imbalance between efficiency and injury can be solved with sequential applications involving welladjusted doses (Fagerness & Yelverton, 2000;Lickfeldt, et al, 2001, McCarty et al, 2004Waltz Jr. & Whitwell, 2005;Ervin & Zhang, 2007;McCullough et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…of trinexapac-ethyl or higher was applied. Fagerness and Yelverton (2000) also found that, when the application of trinexapac-ethyl was carried out in a sequential manner, reductions in the dry biomass of the aerial part were approximately 40%.…”
Section: It Is Observed Inmentioning
confidence: 90%